Proposal for a process oriented knowledge management system (PKMS). (2016) - Louis-Sidney, Ludovic; Cheutet, Vincent; Lamouri, Samir
In an increasingly competitive environment, manufacturing companies are more frequently looking to handle the knowledge referentials relating to their redesign processes. They are then able to implement this with less effort and balance out their work capacity for innovation activities, contributing to more significant improvements in their product offering. In this article we propose a conceptual model for the implementation of a process-oriented knowledge tool dedicated to the formalisation of this type of knowledge referential. The implementable nature of this model has been validated by a demonstrator tested on an application case provided by our industrial partner, Renault Powertrain Technology Department.